2017
DOI: 10.1523/jneurosci.1875-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

APLP1 Is a Synaptic Cell Adhesion Molecule, Supporting Maintenance of Dendritic Spines and Basal Synaptic Transmission

Abstract: The amyloid precursor protein (APP), a key player in Alzheimer's disease, belongs to the family of synaptic adhesion molecules (SAMs) due to its impact on synapse formation and synaptic plasticity. These functions are mediated by both the secreted APP ectodomain that acts as a neurotrophic factor and full-length APP forming trans-cellular dimers. Two homologs of APP exist in mammals: the APP like proteins APLP1 and APLP2, exhibiting functions that partly overlap with those of APP. Here we tested whether APLP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
117
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(123 citation statements)
references
References 91 publications
6
117
0
Order By: Relevance
“…, 2009 ; Mayer et al. , 2016 ; Schilling et al. , 2017 ) although, until now, little evidence of protein–protein trans interactions (i.e., among proteins from two different cells at a junction) has been provided in living cells ( Soba et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2009 ; Mayer et al. , 2016 ; Schilling et al. , 2017 ) although, until now, little evidence of protein–protein trans interactions (i.e., among proteins from two different cells at a junction) has been provided in living cells ( Soba et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2012 ; Shariati and De Strooper, 2013 ). All three proteins are pre- and postsynaptically expressed and up-regulated during postnatal development ( Schilling et al. , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies we could show that cis-directed dimerization of APP alters its subcellular localization and lowers amyloid b production (Eggert et al 2009(Eggert et al , 2018, while trans-directed dimerization of APP and APLP1 impacts intercellular contacts (Soba et al 2005;Kaden et al 2008;Wang et al 2009;Isbert et al 2012;Baumkotter et al 2014;Stahl et al 2014;Decock et al 2015;Mayer et al 2016;Schilling et al 2017). For cis-directed dimerization of APP and its paralogues it was shown that zinc decreases sAPP/ APLP levels (Mayer et al 2016) and favor trans-directed dimerization (Dunsing et al 2017).…”
Section: Discussionmentioning
confidence: 96%
“…; Schilling et al . ). For cis‐directed dimerization of APP and its paralogues it was shown that zinc decreases sAPP/APLP levels (Mayer et al .…”
Section: Discussionmentioning
confidence: 97%